Peran Strategis Pendidikan Kewirausahaan Dalam Membentuk Jiwa Enterpreneur Mahasiswa - Trisnawati, Nadia; Rindiani, Natasya; Annur, Saipul; Handayani, Tutut (Jurnal Ilmiah Wahana Pendidikan, 2025)
Entrepreneurship education plays an important role in shaping the character and entrepreneurial skills of students amidst global challenges and high unemployment rates. This study highlights the urgency of entrepreneurship education as a strategic effort in fostering a creative, innovative, and risk-taking spirit in students. Through a qualitative approach based on literature studies, this study examines various literatures that support the role of entrepreneurship education in improving critical thinking skills, building independent businesses, and creating new jobs. Entrepreneurship education not only equips students with technical skills, but also instills character values such as self-confidence, future vision, and the ability to face uncertainty. The results of the study show that entrepreneurship education contributes greatly to shaping students into drivers of change who are able to develop the economy and society sustainably.